Pesquisa por agentes zoonóticos em tatus (Mammalia: Cingulata) da espécie Euphractus Sexcinctus da Caatinga - Oliveira, Ilanna Vanessa Pristo de Medeiros (Universidade Federal Rural do Semi-Árido, 2021)
The participation of tuna in cycles of zoonotic diseases possibly acting as disseminators of pathogens has been studied for decades. The objective of this research was to evaluate the occurrence of Trypanossoma cruzi, Toxoplasma godii, Leishmania spp. and Leptospira spp. in tatus of the species Euphractus sexcinctus captured in caatinga regions in the state of Rio Grande do Norte, in northeastern Brazil. Twenty animals of this species were captured from which samples of whole blood and tissues of kidneys, liver, spleen, heart and lung were collected for PCR, Blood Culture and Microscopic Seraglutination. Blood culture and blood and cardiac tissue PCR were used for T. cruzi; for T. gondii research, the molecular PCR test of spleen, heart and lung was performed; identification of Leishmania spp. Spleen and liver PCR was performed and microscopic seraglutination and qPCR were performed for investigation of Leptospira spp. infection. All our results were negative, except for one animal that was positive for Chagas disease in blood PCR, with no statistical relevance. The absence of infection may indicate that the control of pathogens within urban and human cycles influences the occurrence of diseases in wild environment animals in the same region, which also raises the hypothesis that there is a direct relationship between human and tuna infections
Keywords: Zoonoses; Tatu-peba; Nordeste; Brasil; Zoonosis; Six-banded armadillo; Northeast; Brazil; CIENCIAS AGRARIAS::MEDICINA VETERINARIA